ChemInform Abstract: New Polymorph of InVO4: A High‐Pressure Structure with Six‐Coordinated Vanadium. Issue 3 (21st January 2014) - Errandonea, Daniel; Gomis, Oscar; Garcia‐Domene, Braulio; Pellicer‐Porres, Julio; Katari, Vasundhara; Achary, S. Nagabhusan; Tyagi, Avesh K.; Popescu, Catalin
Abstract High‐pressure XRD and Raman spectroscopy on orthorhombic InVO4 (space group Cmcm, Z = 4) reveal the existence of a new wolframite‐type polymorph of InVO4 near 7 GPa.